Organizations : structures, processes, and outcomes - Hall, Richard H. (Englewood Cliffs, N.J. : Prentice Hall ; London : Prentice-Hall International, 1991)
For the undergraduate or graduate Sociology of Organizations course taught in Sociology or Business departments, this title is based upon classical and contemporary theory and empirical research and forms a sociological analysis of organizations, focusing on the impacts that organizations have upon individuals and society.
Includes bibliographical references and indexes.
oif 25/03/15
Loan
Keywords: Organizational behavior; Organizational change; Organizational sociology